Pengaruh Literasi Keuangan, Keuangan Digital dan Inklusi Keuangan Terhadap Kinerja Keuangan UMKM di Yogyakarta - Yulaiha, Ambar Ilham; Hermuningsih, Sri; Kusumawardhani, Ratih (Gorontalo State University, 2025)
This study examines the influence of financial literacy, digital finance, and financial inclusion on the financial performance of MSMEs in Yogyakarta. Data were collected from MSME owners through online questionnaires. The results show that MSMEs with good financial literacy, utilize digital finance, and have broad financial inclusion tend to have better financial performance. These findings are relevant given the increasing importance of the role of MSMEs in regional and national economies.